2011
DOI: 10.3892/ijmm.2011.721
|View full text |Cite
|
Sign up to set email alerts
|

miRNA expression profiling identifies DSPP regulators in cultured dental pulp cells

Abstract: Abstract. Dentin sialophosphoprotein (DSPP), an important marker of odontoblast differentiation, is a prerequisite for tooth development and mineralization; however, the molecular mechanisms of both temporal and spatial regulation remain unknown. MicroRNAs (miRNAs) provide an additional level of control beyond that of transcription factors, which regulate post-transcriptional control of gene expression. The present study was designed to provide a first attempt at an in-depth analysis of dental pulp cells at va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
5
1
Order By: Relevance
“…Previous studies had revealed that ITGA5 forced expression by lentivirus or the priming peptide enhanced the osteogenic capacity of human MSC osteoblast (Hamidouche et al, 2009) and human periodontal ligament stem cells (PDLSCs; Wang et al, 2018), which are opposite to the present study. In the present study, however, we had found there was no significant difference between the ITGA5 lentivirus forced expression group and the control group (data not Since the discovery of DPSCs, a mass of research has focused on the proodontogenic effect of different genes or conditions (Cui et al, 2014b;Huang et al, 2011;Ma et al, 2012). However, most of them only reported the proodontogenic effect without further investigation and validation of the involved mechanisms.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Previous studies had revealed that ITGA5 forced expression by lentivirus or the priming peptide enhanced the osteogenic capacity of human MSC osteoblast (Hamidouche et al, 2009) and human periodontal ligament stem cells (PDLSCs; Wang et al, 2018), which are opposite to the present study. In the present study, however, we had found there was no significant difference between the ITGA5 lentivirus forced expression group and the control group (data not Since the discovery of DPSCs, a mass of research has focused on the proodontogenic effect of different genes or conditions (Cui et al, 2014b;Huang et al, 2011;Ma et al, 2012). However, most of them only reported the proodontogenic effect without further investigation and validation of the involved mechanisms.…”
Section: Discussioncontrasting
confidence: 65%
“…Since the discovery of DPSCs, a mass of research has focused on the proodontogenic effect of different genes or conditions (Cui et al, ; Huang et al, ; Ma et al, ). However, most of them only reported the proodontogenic effect without further investigation and validation of the involved mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was found that several miRNAs, including miR-32, miR-885-5, and miR-586, are differentially expressed during the odontoblast differentiation of DPCs (Figure 4B ). Although these miRNAs can be found in both undifferentiated and differentiated DPCs, their levels decrease considerably under mineralization induction, which corresponds with the highest levels of DSPP expression, a prerequisite for initiating mineralization events (Huang et al, 2011 ).…”
Section: Role Of Mirnas In Human Dental-derived Mesenchymal Stem Cellmentioning
confidence: 99%
“…This corresponds to recent reports indicated this miRNA become lowest level compare to the other miRNAs (mir-32, mir-885-5p), when DSPP was the peak level. Moreover, the undetected level might cause by this candidate miRNA derived from study that has experiment on human dental pulp cells (56).…”
Section: Chapter 4 Discussionmentioning
confidence: 99%
“…In addition to the well-known signaling factor, according to enamel mineralization, Fan et al reported that miR-224 can bind to the 30UTRs of Slc4a4 and cystic fibrosis transmembrane conductance regulator mRNAs, which are highly expressed during ameloblast differentiation as ion transporters to maintain pH homeostasis and support enamel mineralization (54). About dentinogenesis, Huang et al, identified that the Dentin sialophosphoprotein (DSPP), an important marker (55), expression of dental pulp cells is regulated post-transcriptionally by miR-32, miR-885-5p, and miR-586 during odontoblast differentiation, although the complex regulatory network between miRNA and mRNAs remains to be determined (56). In additional studies, Heair et al, also found that miR-665 as a potential repressor of odontoblast maturation by contribute to the alteration in the chromatin status of DSPP and Dmp1 by targeting Kat6a expression and also directly targeted Dlx3 mRNA and decreased DLX3 expression and its downstream targets (Runx2,Osx,DSPP) in mouse odontoblasts (57).…”
Section: Table 1 Mirnas In Tooth Development (44)mentioning
confidence: 99%